In Situ Imaging of Candida albicans Hyphal Growth via Atomic Force Microscopy - Arzu Çolak (American Society for Microbiology, 2020)
ABSTRACT Candida albicans is an opportunistic fungal pathogen of humans known for its ability to cause a wide range of infections. One major virulence factor of C. albicans is its ability to form hyphae that can invade host tissues and cause disseminated infections. Here, we introduce a method based on atomic force microscopy to investigate C. albicans hyphae in situ on silicone elastomer substrates, focusing on the effects of temperature and antifungal drugs. Hyphal growth rates differ significantly for measurements performed at different physiologically relevant temperatures. Furthermore, it is found that fluconazole is more effective than caspofungin in suppressing hyphal growth. We also investigate the effects of antifungal drugs on the mechanical properties of hyphal cells. An increase in Young’s modulus and a decrease in adhesion force are observed in hyphal cells subjected to caspofungin treatment. Young’s moduli are not significantly affected following treatment with fluconazole; the adhesion force, however, increases. Overall, our results provide a direct means of observing the effects of environmental factors and antifungal drugs on C. albicans hyphal growth and mechanics with high spatial resolution. IMPORTANCE Candida albicans is one of the most common pathogens of humans. One important virulence factor of C. albicans is its ability to form elongated hyphae that can invade host tissues and cause disseminated infections. Here, we show the effect of different physiologically relevant temperatures and common antifungal drugs on the growth and mechanical properties of C. albicans hyphae using atomic force microscopy. We demonstrate that minor temperature fluctuations within the normal range can have profound effects on hyphal cell growth and that different antifungal drugs impact hyphal cell stiffness and adhesion in different ways.